The contributions of rubber plantation to the socio-economic development: a case study on Kanibongan project-rubber smallholders community in Pitas, Sabah - Julius Kodoh; Andy Rusell Mojiol; Walter Lintangah; Mandy Maid; Liew, Kang Chiang (Kuala Lumpur International Agriculture, Forestry & Plantation, 2016)
Sabah is recognized as the poorest state in Malaysia, whilst having numerous rural communities categorized as a hardcore poor especially in the rural district, Pitas. The Kanibongan project involving rubber smallholders in the Pitas district has been developed by the State Government for the purpose of socio-economic development. The main objectives of this study were to determine the effectiveness of the project implementation in addressing the poverty level in the area involved; and to determine the factors driving the smallholders to participate in the project and the problems faced by these smallholders. This study involved five villages, namely, Kampung Masin, Kampung Kutoyon, Kampung Sulakulong, Kampung Simpang Empat and Kampung Simpang. Data was collected with 100% sampling comprising of 195 respondents by using questionnaires and interviews. Based on the results of this study, the average monthly income of the smallholders showed significant improvement up to 30% since its implementation. The main driven factors for smallholder participation in this project were self motivation (94.3%), subsidy incentives programme by LIGS (93.3%), poverty level (92.9%), good rubber prices (90.3%), and family encouragement (88.2%). Whereas the main problems faced by the smallholders were the unstable price of rubber (84.6%) and theft of latex (74.4%). The Kanibongan rubber planting project is considered successful in reducing poverty among the smallholders involved.